Analisis Sistem Klaim Asuransi Pertanian Persfektif Etika Bisnis Islam (Studi Pada Kelompok Tani di Kecamatan Kualuh selatan) - Fajar Dwi Ramadhan Sipa; Fauzi Arif Lubis Fauzi Arif Lubis; Muhammad Syahbudi (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
In general, the purpose of insurance for the agricultural sector is to provide protection or reimbursement against the risk of crop failure due to pests, diseases, or natural disasters. Currently the insurance business is not focused on life insurance, health insurance, or education insurance, but there is insurance for agriculture, namely rice farming insurance (autp). In Insurance, the insurance claim system is a method or method of paying compensation in the event of a loss in something that is insured, but the insurer has the right to determine how to pay compensation to the insured with the terms and mechanisms provided by the insured. However, the insurance business system offered by the insurer must be in accordance with Islamic business ethics as well as morality, containing concrete values and norms that guide and guide human life in all life. Ethics as a critical and rational reflection helps humans act freely, but can be held accountable. This study aims to analyze how the agricultural insurance compensation system works and whether the Claim System is in accordance with Islamic business ethics, a study of existing Lubung Desa farmer groups in Sei Dua Village, Kualuh Selatan District, using a qualitative research method.